2013
DOI: 10.1128/ec.00239-13
|View full text |Cite
|
Sign up to set email alerts
|

SPO71 Encodes a Developmental Stage-Specific Partner for Vps13 in Saccharomyces cerevisiae

Abstract: The creation of haploid gametes in yeast, termed spores, requires the de novo formation of membranes within the cytoplasm. These membranes, called prospore membranes, enclose the daughter nuclei generated by meiosis. Proper growth and closure of prospore membranes require the highly conserved Vps13 protein. Mutation of SPO71, a meiosis-specific gene first identified as defective in spore formation, was found to display defects in membrane morphogenesis very similar to those seen in vps13Δ cells. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 31 publications
(53 reference statements)
5
70
1
Order By: Relevance
“…We see that ama1D cells make rounded PSMs that retain bright Don1-GFP puncta ( Figure 6D, right) as previously shown (Diamond et al 2009;Park et al 2013), at a frequency similar to what was observed in the sps1D and spo77D mutants (Table 1; P-value ,0.0001). We also observe hyperelongated PSMs in ama1D cells ( Figure 6D, left), consistent with previous reports (Diamond et al 2009).…”
Section: Sps1 Has a Dynamic Localization During Sporulationsupporting
confidence: 85%
“…We see that ama1D cells make rounded PSMs that retain bright Don1-GFP puncta ( Figure 6D, right) as previously shown (Diamond et al 2009;Park et al 2013), at a frequency similar to what was observed in the sps1D and spo77D mutants (Table 1; P-value ,0.0001). We also observe hyperelongated PSMs in ama1D cells ( Figure 6D, left), consistent with previous reports (Diamond et al 2009).…”
Section: Sps1 Has a Dynamic Localization During Sporulationsupporting
confidence: 85%
“…More specifically, the yeast vps13Δ cells show a depletion of PtdIns4P levels in prospore membranes. 26,39 Distinct PtdIns-phosphates play essential roles in autophagy at different levels. For example, PtdIns(3,4,5)P 3 is essential for the signaling pathway that regulates TORC1 (TOR complex 1), and PtdIns(4,5)P 2 is required for the formation of autophagosomes originated from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after loss of Vps13p function an in increased cytotoxicity of an expanded polyQ domain in Rnq1p has been detected (10). Recently, Vps13p was shown to be required for prospore membrane morphogenesis through regulation of phosphatidylinositol phosphatases (11,12). Our previous results have established the 450 kDa protein COH1 as an atypical Golgi matrix protein lacking coiled-coil domains that is crucial for Golgi complex organization.…”
mentioning
confidence: 82%